Preferred Mode of Delivery among Pregnant Women, A cross Sectional Survey - Mohammad Mustafa Farooq Khan, Nimra Aslam Khan, Muhammad Talha Mumtaz, Mahnoor Jathol, Sanam Mahmood, Khushbakhat Rashid, (Pakistan Journal of Medical & Health Sciences, 2023)
Back ground: Pregnancy is a time of utter excitement, joy, and anticipation. As expectant mothers prepare for the arrival of their little ones, one of the most significant decisions they will make is choosing a delivery method. This research paper was conducted to provide pregnant women with a comprehensive guide to support them in reaching an informed decision that suits their needs and preferences. Methodology: The study was conducted on 500 pregnant women admitted to various hospitals in Lahore from January 2022 to June 2022. The participants were given a thorough questionnaire that explored their obstetric history, medical conditions, birth preferences, and delivery methods. The data collected were analyzed using SPSS version 27.0. Descriptive statistics were used to summarize numerical data. The Chi-square test was used to evaluate the associations between different categorical variables. A p-value of less than 0.05 was considered statistically significant. Results: Among the females 68% preferred vaginal births, while 32% chose cesarean sections. The most common reasons for choosing vaginal births were a faster recovery time 58%, less postoperative pain 22%, and a lower risk of complications 20%. Implication: This is done through various platforms, including social media campaigns, television adverts, and community outreach programs. By providing expectant mothers with accurate information and sufficient support, healthcare providers can enable them to make informed decisions. This will reduce the risk of unnecessary maternal and infant complications. Conclusion: In conclusion, awareness-raising is crucial to promote informed decision-making by expectant mothers and support safer and healthier childbirths. This research serves as a valuable tool for healthcare providers to provide expectant mothers with accurate information and support to make informed decisions. Keywords: C Section, Vaginal delivery, Mode of delivery, Preference